Disrupted Lives: Caregivers' Experiences of In‐Hospital Cardiac Arrest Survivors' Recovery 5 Years Later - Molly Harrod; Katrina Hauschildt; Lee A. Kamphuis; Peggy R. Korpela; Marylena Rouse; Brahmajee K. Nallamothu; Theodore J. Iwashyna (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2023)
Background Survivors of in‐hospital cardiac arrest (IHCA) experience ongoing physical and cognitive impairments, often requiring support from a caregiver at home afterwards. Caregivers are important in the survivor's recovery, yet there is little research specifically focused on their experiences once the survivor is discharged home. In this study, we highlight how caregivers for veteran IHCA survivors described and experienced their caregiver role, the strategies they used to fulfill their role, and the additional needs they still have years after the IHCA event. Methods and Results Between March and July 2019, semistructured telephone interviews were conducted with 12 caregivers for veteran IHCA survivors. Interviews were transcribed, and content analysis was performed. Patterns within the data were further analyzed and grouped into themes. A predominant theme of “disruption” was identified across 3 different domains including the following: (1) disruption in caregiver's life, (2) disruption in caregiver–patient relationship, and (3) disruption in caregiver's well‐being. Disruption was associated with both positive and negative caregiver experiences. Strategies caregivers used and resources they felt would have helped them adjust to their caregiver role were also identified. Conclusions Caregivers for veteran IHCA survivors experienced a disruption in many facets of their lives. Caregivers felt the veterans' IHCA impacted various aspects of their lives, and they continued to need additional support in order to care for the IHCA survivor and themselves. Although some were able to procure coping strategies, such as counseling and engaging in stress‐relieving activities, most indicated additional help and resources were still needed.